Effect of Histamine H2-Receptor Blockade on Vagally Induced Gastric Secretion in Man. Issue 5930 (31st August 1974) - Carter, D. C.; Forrest, J. A. H.; Werner, M.; Heading, R. C.; Park, J.; Shearman, D. J. C.
Abstract : Metiamide, an antagonist of histamine H2 receptors, was administered intravenously to normal subjects and to patients with a peptic ulcer during vagal stimulation with a constant infusion of insulin. In normal and peptic-ulcer subjects there were reductions of 70% and 71% respectively in gastric-acid output compared with control tests on the same subjects. The decreased acid output resulted from a reduction in both volume of secretion and acid concentration. Metiamide is therefore a potent inhibitor of vagally-induced gastric acid secretion.